Hepatotoxicity of polymeric proanthocyanidins is caused by translocation of bacterial lipopolysaccharides through impaired gut epithelium. (15th April 2023) - Thilakarathna, Wasitha P.D.W.; Langille, Morgan G.I.; Rupasinghe, H.P. Vasantha
Abstract: Polymeric proanthocyanidins (P-PAC) induced hepatotoxicity in C57BL/6 mice. Mice were supplemented with P-PAC alone or with a mixture of probiotic bacteria (PB), Lactobacillus, Bifidobacterium, and Akkermansia muciniphila for 14 consecutive days. The liver tissues of sacrificed mice were analyzed by mass spectrometry to identify and quantify the P-PAC metabolites. Potential P-PAC metabolites, 2-hydroxyphenylacetic acid and pyrocatechol were detected in higher concentrations and 4-hydroxybenzoic acid was detected exclusively in the mice supplemented with P-PAC and PB. Supplementation with P-PAC alone or with PB caused no shift in the α -diversity of mice gut microbiota. P-PAC induced nonalcoholic steatohepatitis in mice through increasing liver exposure to intestinal bacterial lipopolysaccharides by reducing expression of gut epithelial tight junction proteins, claudin-3 and occludin. Lipopolysaccharide concentrations in the livers of mice supplemented with P-PAC were significantly high compared to the control mice. Furthermore, P-PAC downregulated the expressions of claudin-3 and claudin-4 tight junction proteins in cultured Caco-2 cell monolayers. PB biotransformed P-PAC into bioavailable metabolites and potentially reduced the toxicity of P-PAC. The toxicity of P-PAC and their synbiotics need to be critically evaluated for the safety of human consumption. Graphical abstract: ga1 Highlights: Polymeric proanthocyanidins (P-PAC) caused nonalcoholic steatohepatitis in mice. P-PAC reduced the expression of tight junction proteins. Supplementation of P-PAC may have caused impaired gut epithelium. The toxicity mechanism involved translocation of bacterial lipopolysaccharides. Probiotic bacteria biotransformed P-PAC into non-toxic metabolites.